Impact of surgeon's experience on vascular and haemorrhagic vomplications after kidney transplantation - Kulu, Yakup; Tinoush, Parham; Golriz, Mohammad; Khajeh, Elias; Sabagh, Mohammad Sadegh; Ghamarnejad, Omid; Mieth, Markus; Ulrich, Alexis; Hackert, Thilo; Müller, Beat P.; Strobel, Oliver; Michalski, Christoph; et al. (European journal of vascular and endovascular surgery, 2019)
Objective - The aim of this study was to investigate the independent risk factors of vascular and haemorrhagic complications after kidney transplantation (KTx) and to evaluate how the surgeon's experience affects the rate of vascular and haemorrhagic complications. - Methods - After exclusion of paediatric and multi-organ transplantations, 1462 KTx operations between 2000 and 2016 were analysed. Independent risk factors were evaluated by multivariable logistic regression analysis. The generalised estimating equation logit model was used to display learning curve progression and determine the best cut off number of KTx operations to reduce vascular and haemorrhagic complications. - Results - Vascular and haemorrhagic complications occurred in 38 KTx cases (2.6%). Renal vein thrombosis was the most common complication (0.6%). Graft loss occurred in 11 of 38 (28.9%) cases. Donor age of >60 years (OR 3.687, 95% CI 1.663-8.175, p = 0.001), recipient cardiovascular disease (CVD) (OR 2.270, 95% CI 1.071-4.810, p = 0.032), and surgeon's experience (OR 0.875, 95% CI 0.783-0.977, p = 0.018) were independent predictors of vascular and haemorrhagic complications. Twenty-six previous KTx operations are needed to decrease predicted probability of post-KTx vascular and haemorrhagic complications below 2.6%. - Conclusions - The surgeon's experience is an independent risk factor for vascular and haemorrhagic complications after KTx. Acceptable post-operative vascular and haemorrhagic complications are achieved after a minimum of 26 KTx. As a donor age of >60 years and recipient CVD are also independent risk factors for vascular and haemorrhagic complications, it is suggested that these patients should preferably be operated on by surgeons who have performed more than 26 KTx operations.
Available online 17 September 2018
Gesehen am 31.10.2019